Building Excellence: How Transformational Leadership Elevates Madrasa Graduate Quality and Prepares Students for Global Competence (International Journal of Scientific Research and Management (IJSRM), 2024)
This study explores the impact of transformational leadership on the quality of graduates in madrasa education, emphasizing the role of leadership in fostering educational excellence through innovation, empowerment, and holistic development. Utilizing a qualitative approach, the research examines how transformational leadership practices contribute to student engagement, skill enhancement, and overall graduate preparedness for future challenges. Key transformational leadership elements—such as inspirational motivation, individualized consideration, and intellectual stimulation—are analyzed to understand their influence on students’ academic and personal growth. Findings indicate that transformational leadership within madrasas not only enhances academic performance but also equips students with essential competencies and values aligned with global demands. This study highlights the importance of strategic leadership in education, offering insights into how madrasas can elevate graduate quality through effective leadership practices.